Prevalence and factors associated with infection in patients with diabetes mellitus who underwent amputation (Estima – Brazilian Journal of Enterostomal Therapy, 2024)
Objective: To analyze the prevalence and factors associated with infection in patients with diabetes mellitus who underwent lower extremity amputation. Method: Cross-sectional, retrospective, and analytical study carried out in a high complexity hospital in Teresina, Piauí, with 70 medical records of patients admitted from January 2015 to December 2016. Inferential analysis was performed using χ2 association tests. Pearson and Fisher’s exact, considering p